An Empirical Analysis of Stock Price Risk in Chinese Growth Enterprises Market - A GARCH-VaR Approach - WU, Maoguo; LUO, Xin (European Scientific Journal, ESJ, 2016)
The aim of Growth Enterprises Market (GEM) is to provide financing channels to burgeoning and high-technology companies which cannot be listed in the main board. GEM is a supplement to the main board. As an emerging securities market, GEM shows a unique volatility compared with the main board. The volatility of GEM has connections and differences with the main board market. Studying the price volatility of GEM contributes directly to the healthy growth of GEM and the main board. This paper investigates the risk characteristics of GEM and provides several measures to deal with the risk. In this paper, VaR based on GARCH model is utilized for empirical tests. Therefore, this paper studies the characteristics and the extent of volatility risk of GEM stock price systematically.